Experimental Research of Supersonic Flow Around Simulating Rocket-Ramjet; MATEC Web of Conferences; Vol. 23 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment - Maslov E. A. Evgeny Anatolievich (2015, 2015)
Title screen